Prediksi Kebangkrutan Dengan Metode Altman Z-Score Dalam Persepsi Maqashid Syariah - Aulia Rahmah; Kamilah Kamilah (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the prediction of bankruptcy using the Altman Z-Score method with maqashid sharia analysis. The study was conducted on 6 (six) food and beverage companies listed on the Indonesia Stock Exchange by accessing the www.idx.co.id site for the 2018-2020 period. The method used is a qualitative research method with a descriptive approach and uses secondary data. The data analyzed are in the form off annual financial reports from 6 food and beverage companies thet have sharia shares listed on the Indonesia Stock Exchange (IDX).